2003
DOI: 10.1210/jc.2003-030349
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Bioactivity in Fo-Ti and Other Herbs Used for Their Estrogen-Like Effects as Determined by a Recombinant Cell Bioassay

Abstract: One of the most important issues in women's health concerns the risks and benefits of estrogen replacement therapy. Continual uncertainty and lack of consensus regarding estrogen replacement therapy has driven many women to seek alternative sources of estrogen, including herbal remedies. We adapted a recombinant cell bioassay to measure estrogen bioactivity in herbs. We studied, in vitro, estrogen bioactivity in red clover, dong quai, black cohosh, soy, licorice, chaste tree berry, fo-ti, and hops. Soy, clover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…[72] In a study to assess the estrogen bioactivity of some herbs, Oerter Klein et al . [73] found that soy, clover, licorice, hops, and fo-ti to have high estrogen activity, while chaste tree berry, black cohosh and dong quai did not have measurable estrogen activity. They further found that removal of the glycone group from soy increases its estrogen bioactivity significantly.…”
Section: Treatment Of Postmenopausal Osteoporosis By Phytoestrogensmentioning
confidence: 99%
“…[72] In a study to assess the estrogen bioactivity of some herbs, Oerter Klein et al . [73] found that soy, clover, licorice, hops, and fo-ti to have high estrogen activity, while chaste tree berry, black cohosh and dong quai did not have measurable estrogen activity. They further found that removal of the glycone group from soy increases its estrogen bioactivity significantly.…”
Section: Treatment Of Postmenopausal Osteoporosis By Phytoestrogensmentioning
confidence: 99%
“…Studies conducted after 1990 using purified black cohosh free of estrogenic adulterants [14] have generally not demonstrated classical estrogen-like effects on target cell activity in various animal or in vitro models [15-19] or in clinical studies [9, 20], although modest protective effects on bone in postmenopausal women have been reported [11]. Moreover, estrogen receptor binding studies [21-24] have generally failed to reveal any interactions with ligands of the estrogen receptor (ER) in breast and uterine cells. Paradoxically, black cohosh extract has been shown to inhibit the estrogen-dependent MCF-7 mammary tumor cell proliferation and to enhance inhibition with tamoxifen, suggesting an estrogen antagonist, anti-tumor effect on the breast [19, 25, 26].…”
Section: Introductionmentioning
confidence: 99%
“…In general, estrogens induce a decrease in LH or FSH, increase uterine weight and vaginal cytology, compete estradiol binding to uterine cytosol or recombinant ER, stimulate ERE-reporter assays, ER responsive genes, promote estrogen responsive tumor growth in vivo and in vitro , increase or decrease bone formation or resorptive markers, and increase bone density.1(Duker et al 1991),2(Seidlova-Wuttke et al 2003a),3(Freudenstein et al 2002),4(Liske et al 2002),5(Zhang et al 2003),6(Einer-Jensen et al 1996),7(Amato et al 2002),8(Burdette et al 2003, Burdette et al 2002),9(Wuttke et al 2003),10(Kretzschmar et al 2005),11(Jarry et al 1985),12(Jarry et al 1995),13(Liu et al 2001),14(Onorato and Henion, 2001),15(Zierau et al 2002),16(Beck et al 2003),17(Lupu et al 2003),18(Oerter Klein et al 2003),19(Wober et al 2003),20(Bennetau-Pelissero et al 2004),21(Viereck et al 2005),22(Nisslein and Freudenstein, 2004),23(Nisslein and Freudenstein, 2003b),24(Kruse et al 1999),25(Dixon-Shanies and Shaikh, 1999),…”
Section: Figurementioning
confidence: 99%
“…A third study found that BCE competed with estradiol for binding to ERs in uterine cytosol but not to recombinant ERs, confirming the first two seemingly conflicting reports (Jarry et al 1995). BCE does not induce transcription in estrogen response element reporter assays in yeast (Oerter Klein et al 2003, Beck et al 2003), or induce estrogen responsive genes in mammalian endometrial or breast cells, or trout liver cells (Liu et al 2001, Bennetau-Pelissero et al 2004). BCE does not induce the proliferation (i.e.…”
Section: Introductionmentioning
confidence: 99%